Investigating the success factors for reward-based crowdfunding campaigns - Daskalakis, Nikolaos; Karpouzis, Efstathios; Benis, Dimitrios; Angelakis, Antonios (Journal of Entrepreneurship, Business and Economics; Vol 11 No 1 (2023), 2023)
The main objective of this paper is to explore the success factors of reward-based crowdfunding campaigns, over a long time-period, and using a large dataset of campaigns. Specifically, we use a dataset of 179,066 Kickstarter campaigns, covering the period 2009-2021. We run probit and logit regressions to identify the success factors. Our main findings are the following; the number of backers and the average amount per backer are positively related to the project’s success, while the target goal is negatively related to success. We also find that the total number of words used to describe a campaign is not an important success factor, contrary to the academic literature. Last, we find that US projects are more likely to lead to success than non-US projects. Research paper Keywords: Reward-Based Crowdfunding, Success Factors, Probit-Logit Reference to this paper should be made as follows: Daskalakis, N., Karpouzis, E., Benis, D. & Angelakis, A. (2023). Investigating the success factors for reward-based crowdfunding campaigns. Journal of Entrepreneurship, Business and Economics , 11 (1), 134–152.